Whole blood DNA methylation signatures of diet are associated with cardiovascular disease risk factors and all-cause mortality - Ma, Jiantao; Schöttker, Ben; Brenner, Hermann (Circulation. Genomic and precision medicine, 2020)
Background: DNA methylation patterns associated with habitual diet have not been well studied. Methods: Diet quality was characterized using a Mediterranean-style diet score and the Alternative Healt